Shrinkage phenomena in silumins when treated with long‑acting modifiers - A. A. Andrushevich; M. A. Sadokha (Литьë и металлургия)
The influence of various modifying additives on the shrinkage porosity of silumins and the tightness of castings is considered. A comparative assessment of the modification of the shrinkage components in the resulting blanks was carried out. The dependences of the strontium content in the silumin melt depending on the melt holding time are established. The relationship between the level of scrap of aluminum castings and the content of strontium has been revealed. Due to the fact that the level of rejection of aluminum castings due to leakiness does not directly depend on the porosity in the alloy, it is suggested that strontium has significant changes in the mechanism of crystallization of the alloy and the distribution of microporosity in the alloy structure with the formation of a more developed channels.